2004
DOI: 10.1080/0958315031000151693
|View full text |Cite
|
Sign up to set email alerts
|

Non-Susceptibility of EarthwormEiseniafetidato the Rhabditid NematodePhasmarhabditishermaphrodita, a Biocontrol Agent of Slugs

Abstract: The rhabditid nematode Phasmarhabditis hermaphrodita is a lethal parasite for slugs that is sold commercially in Europe under the trade name Nemaslug TM . We evaluated the effects of P. hermaphrodita on the earthworm Eisenia fetida (Savigny). Adults of E. fetida were exposed in one-liter glass beakers to P. hermaphrodita at three concentrations (1)/, 10)/ and 50 )/ of the field recommended rate of 3)/10 9 billion nematodes/ha) during a 14-day period in an artificial soil substrate. The average body weight, bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…All three species of Phasmarhabditis used in this report were isolated from slugs recovered from nurseries and garden centers located in the state of California. In the case of P. hermaphrodita (Nemaslug 1), studies showed it does not cause mortality to some non-target organisms like Ariolimax columbianus Gould, 1851; Pomatias elegans Müller, 1774; Monacha cantiana Montagu, 1803; Eisenia fetida Savigny,1826; and Lumbricus terrestris Linnaeus, 1758 [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…All three species of Phasmarhabditis used in this report were isolated from slugs recovered from nurseries and garden centers located in the state of California. In the case of P. hermaphrodita (Nemaslug 1), studies showed it does not cause mortality to some non-target organisms like Ariolimax columbianus Gould, 1851; Pomatias elegans Müller, 1774; Monacha cantiana Montagu, 1803; Eisenia fetida Savigny,1826; and Lumbricus terrestris Linnaeus, 1758 [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Some other snails (Succinaea putris, Pomatias elegans, Cepaea nemoralis and others) can be infected with P. hermaphrodita but its effect on them is very low, if any. Negative effect on the earthworms Lumbricus terrestris and Eisenia foetida and others has never been found [134,135], and no effect was found also against insects Pterostichus melanarius, Zophobas morio or Galleria mellonella [136,137]. P. hermaphrodita is freely associated with many soil-dwelling bacteria [55,138], and some of them, for example, Stenotrophomonas maltophilia [42] can be occasionally dangerous for human, especially those with a weakened immunity system.…”
Section: Phasmarhabditis Hermaphroditamentioning
confidence: 99%
“…It does not kill US strains of the earthworms Lumbricus terrestris L 35. and Eisenia fetida (Savigny)36 or UK strains of L. terrestris, Eisenia hortensis (Michaelsen), E. fetida, Eisenia andrei Bouche, Dendrodrilus rubidus (Savigny) or the platyhelminth Arthurdendyus triangulatus (Dendy) (the New Zealand flatworm) 37. These results appear to contradict an earlier study in which L. terrestis were found parasitised by a ‘ Phasmarhabditis ‐like’ species in the USA,38 but it may be that the nematode isolated was not a Phasmarhabditis spp.…”
Section: Non‐target Organismsmentioning
confidence: 99%